Effect of source gases on CVD synthesis of CNTs@TiB2 composite powders using Ni/Y2O3 as the catalyst. Issue 8 (1st June 2020) - Lin, Jia; Yang, Yihang; Zhang, Houan; Li, Fenqiang
Abstract: Carbon nanotubes (CNTs) were in-situ grown on TiB2 substrates via CVD using Ni/Y2 O3 as catalysts. The effects of methane (CH4 ), acetylene (C2 H2 ), and carbon monoxide (CO) gas as the carbon source on the quality and quantity of the carbon products was studied and compared using XRD, SEM, TEM, and Raman characterization techniques. Using C2 H2 showed the highest carbon yield, which was due to the increasing amount of impurities. Combined with the results of TEM and Raman spectroscopy, the CNTs formed in C2 H2 or CO gas exhibit more defects. Although the amount of products formed in CH4 gas is smaller, the purity and graphitization of CNTs are much higher than that formed in C2 H2 or CO gas. The difference can be attributed to the different thermal stabilities of CH4, C2 H2, and CO. Since CH4 possesses a basic structure and exhibits higher chemical stability at high-temperature, high-purity and high-quality CNTs are more likely to grow in CH4 gas rather than C2 H2 and CO. Due to the comparative instability of C2 H2 and CO, they have been found to be more reactive, which leads to increased decomposition and the formation of impurities and defects, in addition to the CNTs.